Genome sequence of idiomarina sp strain a28l, isolated from pangong lake, india - Gupta, Hemant Kumar; Singh, Ajit; Sharma, Rakesh (Journal of Bacteriology, 2011)
Idiomarina sp. strain A28L was isolated from the alkaline brackish water of a high-altitude lake, Pangong Lake. Here, we present the draft genome of Idiomarina sp. strain A28L, which contains 2,591,567 bp with a G + C content of 45.5 mol% and contains 2,299 protein-coding genes and 56 structural RNAs.